2020
DOI: 10.1002/fsn3.1633
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative conversion of lignin isolated from wheat straw into aromatic compound catalyzed by NaOH/NaAlO2

Abstract: Lignin was isolated from wheat straw via organosolv process and further transferred to monophenolic compounds via oxidative conversion. Wheat straw lignin (WSL) with purity at 91.4 wt% was acquired in the presence of heterogeneous and recyclable catalyst of Amberlyst‐45. WSL was characterized by infrared spectrometer (IR), nuclear magnetic resonance spectroscopy (NMR) including 1 H NMR and 13 C NMR spectra. The results showed that WSL possesses typical syringyl (S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Although many studies are being conducted, on the idea of using nanomaterials for enhancing oil recovery (EOR) there are still several obstacles that prevent its widespread implementation at the field scale (Kazemzadeh et al 2019 ; Afolabi 2018 ; Davoodi et al 2022 ). The difficulty in determining the number of nanoparticles to be used, the lack of available data for predictive modeling, the high production cost of nanoparticles combined with the huge capital investment in extraction of hydrocarbons, the lack of clear mechanisms with supported solid evidence, formation heterogeneity, the difficulty in attaining stability of nanoparticles are some of the challenges faced in the oil and gas industry that hinder in the full field application of nano-EOR (nano-enhanced oil recovery) methods, a rise in rheological characteristics and expense as a result of pipe obstruction, and sometimes results in pipe breakage and crude oil leaks, posing significant environmental difficulties (Leng et al 2019 ; Satyarthi et al 2011 ; Alsabagh et al 2016 ; Luo et al 2020 ; Zehua and Xiutai 2015 ; Huaping et al 2006 ; Abdelhamid et al 2021 ). The authors can be thought in ability of produced low cost aromatic materials from agricultural waste via MW/US lignin isolation as outlined in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies are being conducted, on the idea of using nanomaterials for enhancing oil recovery (EOR) there are still several obstacles that prevent its widespread implementation at the field scale (Kazemzadeh et al 2019 ; Afolabi 2018 ; Davoodi et al 2022 ). The difficulty in determining the number of nanoparticles to be used, the lack of available data for predictive modeling, the high production cost of nanoparticles combined with the huge capital investment in extraction of hydrocarbons, the lack of clear mechanisms with supported solid evidence, formation heterogeneity, the difficulty in attaining stability of nanoparticles are some of the challenges faced in the oil and gas industry that hinder in the full field application of nano-EOR (nano-enhanced oil recovery) methods, a rise in rheological characteristics and expense as a result of pipe obstruction, and sometimes results in pipe breakage and crude oil leaks, posing significant environmental difficulties (Leng et al 2019 ; Satyarthi et al 2011 ; Alsabagh et al 2016 ; Luo et al 2020 ; Zehua and Xiutai 2015 ; Huaping et al 2006 ; Abdelhamid et al 2021 ). The authors can be thought in ability of produced low cost aromatic materials from agricultural waste via MW/US lignin isolation as outlined in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since many years ago, nitroaromatics have been common reactants or intermediates in many industrial processes, especially for the synthesis of drugs and dyes. [2,3] During these processes, the extra or unreacted nitrobenzene derivatives remain in the waste and could leak into the water, soil and other parts of nature. It was reported that this leakage reaches 10 million kg in a year.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of nitroaromatic compounds to their amino derivatives is a classic method to remove the toxic nitroaromatics and convert them to more useful and valuable compounds [1] . Since many years ago, nitroaromatics have been common reactants or intermediates in many industrial processes, especially for the synthesis of drugs and dyes [2,3] . During these processes, the extra or unreacted nitrobenzene derivatives remain in the waste and could leak into the water, soil and other parts of nature.…”
Section: Introductionmentioning
confidence: 99%
“…The former could be converted into cellulose nanocrystals [8], glucose [11], cellulose acetate [12] and HMF [4], and the latter could be converted to phenolic monomers via catalytic oxidation [13]. The isolation of cellulose and lignin from lignocellulosic biomass has attracted considerable attention as the shortage of fossil resources becomes more and more serious [14].…”
Section: Introductionmentioning
confidence: 99%